Inhibition of 13-cis retinoic acid-induced gene expression of reactive-resistance genes by thalidomide in glioblastoma tumours in vivo - Milanović, Dušan; Sticht, Carsten; Röhrich, Manuel; Maier, Patrick; Herskind, Carsten (OncoTarget, 2015)
Oncotarget | https://doi.org/10.18632/oncotarget.4727 Dusan Milanovic, Carsten Sticht, Manuel Röhrich, Patrick Maier, Anca-L Grosu, Carsten Herskind
Gesehen am 20.03.2018